ANALISIS SEKTOR UNGGULAN DI PROVINSI NUSA TENGGARA BARAT TAHUN 2014-2023: (ANALISIS SEKTOR UNGGULAN DI PROVINSI NUSA TENGGARA BARAT TAHUN 2014-2023) - Arianto, Arif Risky Wahyu; Cahyono, Hendry (Universitas Negeri Surabaya, 2025)
Economic growth instability in many countries is often caused by an emphasis on increasing output figures without sufficient regard for efficiency and sustainability. This study aims to identify the leading and high-potential economic sectors in West Nusa Tenggara Province that can drive its economic growth. It employs a descriptive research design with a quantitative approach, utilizing Location Quotient, Dynamic Location Quotient, Shift Share, and Klassen Typology analyses.The LQ and DLQ analyses reveal that the Education Services sector as well as the Mining and Quarrying sector function both as basic and prospective industries. The Shift-Share analysis shows a positive national growth effect for every sector; in particular, Education Services, Financial Services and Insurance, and Wholesale and Retail Trade demonstrate rapid growth and strong competitive advantage. Finally, the Klassen Typology analysis indicates that Wholesale and Retail Trade, Construction, and Mining and Quarrying are classified as advanced and fast-growing sectors.